2010
DOI: 10.1007/s11033-010-0078-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of methionine synthase (Sal k 3), as a novel allergen of Salsola kali pollen

Abstract: Salsola kali pollen is a common cause of pollinosis during summer and early fall in desert and semi-desert regions. The aim of this study was the identification and characterization of Sal k 3, a new allergen from S. kali pollen. S. kali pollen extract was fractionated by SDS-PAGE and the allergenic profile was determined by IgE-immunoblotting using twelve S. kali allergic patients. Protein identification was carried out by the means of mass spectrometry. Using degenerated primers, two DNA fragments encoding N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…It was thus suggested that probable cysteine residues of the pollen proteins may be associated with interchain disulfide bonds. In previous studies, it was demonstrated that some proteins in pollen extract such as methionine synthase of S. kali or A. retroflexus were partially degraded into two fragments with approximate MWs of 45 and 39 kDa [19, 20]. Taken together, these observations suggested that some proteins in Acacia pollen extract are susceptible to degradation as a result of proteolysis or exposure to a reducing condition.…”
Section: Discussionmentioning
confidence: 90%
“…It was thus suggested that probable cysteine residues of the pollen proteins may be associated with interchain disulfide bonds. In previous studies, it was demonstrated that some proteins in pollen extract such as methionine synthase of S. kali or A. retroflexus were partially degraded into two fragments with approximate MWs of 45 and 39 kDa [19, 20]. Taken together, these observations suggested that some proteins in Acacia pollen extract are susceptible to degradation as a result of proteolysis or exposure to a reducing condition.…”
Section: Discussionmentioning
confidence: 90%
“…Q8L5K9), methionine synthase Sal k 3 [14], the profilin Sal k 4 [15,16], the Ole e 1-like protein Sal k 5 and the major allergen and S. kali- specific marker Sal k 1, the subject of this study [11]. …”
Section: Discussionmentioning
confidence: 99%
“…Several allergens from C. album (Che a 1 [12], Che a 2 and Che a 3 [13]) and S. kali [Sal k 1 [11], Sal k 2 (accession No. Q8L5K9), Sal k 3 [14], Sal k 4 [15,16] and Sal k 5 [17]] pollens have been identified (for a review, see [18]). Sal k 1 is the allergenic marker of S. kali pollen able to discriminate between sensitized and nonsensitized patients to this weed [11].…”
Section: Introductionmentioning
confidence: 99%
“…Three allergens have been identified and characterized in C. album pollen: Che a 1, a member of the Ole e 1-like protein family, the profilin Che a 2 and the polcalcin Che a 3 [7] . Regarding S. kali allergens, Sal k 1, a pectin methylesterase, has been described as a major allergen and specific marker of S. kali pollen allergy [9], and the minor allergens reported, Sal k 3, a methionine synthase [13] and the profilin Sal k 4 [14,15]. In addition, sera of patients allergic to S. kali contain IgEs able to bind to other proteins in immunoblotting with high frequency, such as 19- or 25-kDa bands that are recognized by a significant number of patients from several Spanish populations.…”
Section: Introductionmentioning
confidence: 99%